Pembelajaran Al-Qur’an dengan Metode An-Nahdliyah pada Era Pandemi Covid-19 (Studi Kasus di TPQ Al-Mubarok Dusun Sri Lestari Kampung Sriwijaya Mataram) - Rohman, Syaifur (Fitrah: Journal of Islamic Education, 2021)
The method is an important part of the learning component, including learning the Qur'an. Uniquely, in the Bandar Mataram District area, they began to apply a "new" method in teaching the Koran to children, namely the an-Nahdhiyah method. This study seeks to describe the application of the an-Nahdliyah method in learning the Koran in the pandemic era, with the research background at TPQ Al-Mubarok, Sri Lestari Hamlet, Sriwijaya Village, Mataram. This empirical research uses a qualitative approach with a case study method. Direct observation techniques and structured interviews were used to obtain research data. Furthermore, the data were analyzed using data reduction techniques, data presentation and conclusion drawing. Finally, test the validity of the data through triangulation techniques. The results of this study indicate that (1) the use of the an-Nahdliyah method is quite effective in providing guidance and learning of the Qur'an to children, because the method is fun, not boring, and uses the beat of a classical stick; and (2) the application of the an-Nahdliyah method is carried out in 3 (three) stages, namely the letter recognition stage, the stage of understanding the beat as murottal reading, and the stage of reading together.